THE DIFFERENCE OF LEARNING ENGLISH RESULTS BY USING THE BASED GENRE AND CONCEPT SENTENCE IN BASIC SCHOOL - Nur Indah Mardiana; Naeklan Simbolon (FIP Unimed, 2020)
This study aims to determine student learning outcomes in English subjects using Genre Based and Concept Sentence in elementary schools. This research was conducted in one of the SD Medan. This research is a quasi experiment. The population in this study were all fourth grade students of SD IT Ummi Aida Medan. The sample consisted of 40 students. The data collection technique used was a test. The data collection instrument used was a test of English learning outcomes in the form of multiple choices of 30 questions. Before the research was carried out, the researchers tested the validity, reliability, and level of difficulty. The results showed that the experimental 1 average score was 78.75 and the experimental 2 average score was 68. Hypothesis testing using the t-test, obtained tcount> ttable (2.67> 2.02), with a significant level of α = 0.05. The results of the study concluded that there were differences in the learning outcomes of fourth grade students in English using Genre Based and Concept Sentence.